Economia da informação, custos de transação e produtividade: um ensaio sobre os retornos das tecnologias de informação - Tagnin, Fabio (2004)
The feeling that investments in technology -must increase work productivity has been raising questions addressed in many studies in the past years, but no positive correlation between these applications and firms' revenues have been found. However, it has also been supported by several other authors who have gathered empirica! evidences attesting that the returns from IT investments must be measured by other variables, distinct from aggregate economic industry data. We attempt to analyze this dilemma in the light of Information Economics, testing the hypothesis that well planned innovations in business processes and organizational structure, supported by information technology, do add value and increase firms' productivity and efficiency. Our analysis focuses on the transaction costs of business processes, setting these costs as the core of any productivity variables with which one could measure, with some precision, the impact of new technological resources added to the focal processo